Preparation method and application of three-dimensional covalent organic framework 3D COF materials based on 8-connected cubic ligands
Through the preparation of a 3D COF material of a three-dimensional covalent organic frame based on 8-connected cubic ligand, the electrochemical performance problems caused by dense stacking of the negative electrode material layer structure of lithium-ion battery are solved, and higher specific capacity, stability and safety are achieved .
Patent Information
- Application Number
- CN202310228926.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-10
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-03-10
AI Technical Summary
The existing lithium-ion battery negative electrode materials have poor transferability of unidirectional one-dimensional pore channels and buried active sites caused by dense stacking of layer structures, which affect their electrochemical performance.
Using the preparation method of a 3D covalent organic frame 3D COF material based on 8-connected cubic ligand, 3D with interpenetrating three-dimensional topology and high-connected permanent voids are formed by combining 8-connected 3D high-connected building blocks and TTEP and TAPP. COF material.
This material can effectively avoid the accumulation problem of 2D COF materials, evenly distribute rich active sites, provide multi-dimensional ion motion paths, and improve electrochemical performance, including higher specific capacity, better stability and safety.
Smart Images

Figure CN116082591B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of negative electrode materials for lithium-ion batteries, and in particular to a preparation method and application of a three-dimensional covalent organic framework (3D COF) material based on 8-connected cubic ligands. Background Art
[0002] With the continuous development of the industrial age, the world's production capacity has been continuously improved, and the power in its production is mainly provided by non-renewable fossil energy. With the continuous reduction of energy reserves and the continuous rise of emerging industries, it is necessary to develop green and renewable energy, mainly new energy such as solar energy, wind energy, water conservancy and tidal energy. In order to solve the problem of intermittent energy, requirements are put forward for the development of energy storage equipment. Among them, lithium batteries have been rapidly developed and put into practical application due to their high capacity, practicality and stability. At the same time, the development and preparation of electrode materials with high specific capacity, high volume density and safety are of great significance to the development of lithium batteries and their practical application in power and 3C equipment.
[0003] Covalent organic framework compounds (COFs) are a new class of crystalline organic polymers with inherent porosity, structural periodicity and light element components. They construct covalently linked periodic two-dimensional or three-dimensional extended frameworks through organic units. This structural feature makes COFs materials widely studied and applied in many fields such as gas adsorption, luminescence, electrocatalysis, energy storage and semiconductors. In the field of electrochemical energy storage, carbon materials are currently the most widely used negative electrode materials, which have the advantages of abundant reserves, wide sources, low cost and stable electrochemical properties. However, they also have shortcomings such as low first coulombic efficiency, low specific capacity and poor rate performance. They cannot meet the needs of high-performance batteries and cannot adapt to the requirements of high volume density and high specific capacity of today's energy storage devices, so new negative electrode materials need to be developed. COFs materials have achieved rapid development due to their diverse structures, high porosity, high chemical stability and high theoretical capacity. However, most of the traditional COFs material research focuses on 2DCOFs, because their layered structure, rich active sites, high porosity and clear channels are conducive to the transfer and insertion and extraction of charges and lithium ions. However, in practical applications, the actual specific capacity of 2D COFs materials is not ideal. The dense stacking of the layer structure leads to unidirectional one-dimensional (1D) pore channels with minimal transfer and a large number of buried active sites, which to some extent limits their electrochemical performance. In contrast, in 3D COFs materials, the framework structure can avoid the stacking phenomenon of the π plane, which leads to a higher surface area, more uniform active sites and better stability than 2DCOFs, resulting in multiple pathways for ion diffusion and maximum utilization of active sites. However, compared with the rich variety of 2D COFs materials, conjugated 3D COFs are still very rare due to the lack of sufficient conjugated 3D building blocks. Therefore, the development of multi-connected organic ligand building units and the exploration of high-quality synthesis methods are necessary for the development of conjugated three-dimensional COFs, especially for the application of COFs materials in the field of lithium-ion battery negative electrode materials. Summary of the invention
[0004] Purpose of the invention: In view of the problems existing in the prior art, the present invention provides a method for preparing a three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands. The 3D COF material prepared by the present invention has abundant active sites evenly distributed and better structural stability. It can not only serve as an electrochemical active center, but also inhibit the dissolution, stacking and volume expansion of 2D COF materials in organic electrolytes. It can be used as a negative electrode material for new high-performance lithium-ion batteries. As a negative electrode for lithium batteries, it can solve the problems of stacking, poor conductivity and volume expansion of existing electrode materials, and has better stability, capacity and safety.
[0005] The present invention also provides the three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands and its application as a lithium ion negative electrode material.
[0006] Technical solution: In order to achieve the above-mentioned purpose, the preparation method of a three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands described in the present invention comprises the following steps:
[0007] (1) dissolving 3,5-dibromobenzaldehyde and pyrrole in an acidic solvent and heating them to react to generate an intermediate product A;
[0008] (2) reacting product A with p-acylphenylboronic acid to generate product B through Suzuli coupling reaction;
[0009] (3) dissolving product B and 5,10,15,20-tetrakis(4-aminophenyl)porphyrin (TAPP) in an organic solvent, and fully dispersing and dissolving them by ultrasonication;
[0010] (4) adding a catalyst to the mixture of step (3), and then circulating liquid nitrogen to freeze, evacuate, and thaw, and then maintaining the temperature to obtain a suspension;
[0011] (5) After the suspension is cooled to room temperature, the precipitate is collected by centrifugation and dried to obtain the product [8+4] type 3D COF material.
[0012] Wherein, the molar ratio of 3,5-dibromobenzaldehyde to pyrrole in step (1) is 1:1-1:1.2; the acidic solution is acetic acid or propionic acid; the heating temperature is 130°C-150°C; and the reaction time is 2-4 hours.
[0013] Preferably, 3,5-dibromobenzaldehyde and pyrrole are subjected to condensation cyclization under heating to synthesize 5,10,15,20-tetrakis(3,5-dibromophenyl)porphyrin (TDBrEP).
[0014] Preferably, the molar mass ratio of 3,5-dibromobenzaldehyde to pyrrole is 1:1.1, propionic acid is selected as the solvent; the heating temperature is 140° C.; the reaction time is 3 hours; 3,5-dibromobenzaldehyde and pyrrole are heated to undergo condensation cyclization reaction, and the intermediate product A is obtained by suction filtration, washing and drying.
[0015] Wherein, the molar ratio of the product A in step (2) to p-acylphenylboronic acid is 1:8-1:10; the heating temperature of the Suzuli coupling reaction is 80°C-120°C, and the reaction time is 1-3 days; the solvent of the Suzuli coupling reaction is dioxane, tetrahydrofuran and water or dioxane and water.
[0016] Wherein, in step (2) the Suzuli coupling reaction is added with an alkaline metal salt and a catalyst; the alkaline metal salt is Na 2CO 3 , K 2 CO 3 or CsCO 3 The catalyst is tetrakis(triphenylphosphine)palladium(0), AsPh 3 、n-Bu 3 P or Ph 2 P(CH 2 ) 2 PPh 2 (dppe).
[0017] Preferably, product A is reacted with p-acylphenylboronic acid via Suzuli coupling reaction to generate 5,10,15,20-tetrakis(tetrakis(([1,1':3',1"-triphenyl]-4,4"-dicarboxaldehyde)))(TTEP) ligand, and the product is obtained by extraction and spin drying.
[0018] More preferably, the molar ratio of product A to p-acylphenylboronic acid is 1:10; the solvent is tetrahydrofuran and water; the alkaline metal is K 2 CO 3 The catalyst is tetrakis(triphenylphosphine)palladium(0); under argon protection, the reaction temperature is 100°C; the reaction time is 2 days; the extract is dichloromethane, chloroform and ethyl acetate.
[0019] Wherein, the product B in step (3) is 5,10,15,20-tetrakis(tetrakis(([1,1':3',1"-triphenyl]-4,4"-dicarboxaldehyde)))(TTEP) ligand; the molar ratio of TTEP to TAPP is 1:2-1:3; and the organic solvent is one or more of dioxane, N-methylpyrrolidone, N,N-dimethylformamide and 1,3,5-trimethylbenzene.
[0020] Preferably, the molar ratio of TTEP to 5,10,15,20-tetrakis(4-aminophenyl)porphyrin (TAPP) is 1:2; and the organic solvent is N-methylpyrrolidone (NMP) and 1,3,5-trimethylbenzene.
[0021] Wherein, the catalyst in step (4) can be 6M acetic acid.
[0022] In step (4), the liquid nitrogen is rapidly frozen and then vacuumized to an internal pressure of 0.15-0.2 mmHg, and a cycle of liquid nitrogen freezing-vacuuming-thawing is repeated 2-3 times before the reaction is kept warm. The purpose of liquid nitrogen freezing-vacuuming-thawing is to remove oxygen from the reaction solution, thereby achieving a better experimental effect.
[0023] Wherein, the insulation temperature in step (4) is 100-140° C., and the reaction time is 3-7 days.
[0024] Preferably, the temperature of the heat preservation reaction is 120° C. and the reaction time is 5 days.
[0025] Wherein, during the centrifugal separation in step (5), DMF, dichloromethane or tetrahydrofuran and methanol can be used for multiple washings.
[0026] Wherein, the drying in the above steps is vacuum drying, and the vacuum drying temperature is 60°C-120°C.
[0027] The three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands is prepared by the preparation method of the present invention.
[0028] The invention discloses an application of a three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands in the field of negative electrode materials for lithium-ion batteries.
[0029] The present invention proposes a method for preparing a lithium ion negative electrode material based on a three-dimensional covalent organic framework 3D COF material with 8-connected cubic ligands, which can effectively solve the problem that 2D COFs negative electrode materials used for lithium ion batteries have dense stacking of layer structures, resulting in unidirectional one-dimensional (1D) pore channels with small transmissibility and a large number of buried active sites, thereby affecting their actual electrochemical performance. Existing methods such as physical and chemical stripping to avoid stacking cannot completely solve the problem of poor actual specific capacity. 3D COFs materials can fundamentally avoid these problems, but 3D COFs are underdeveloped and the synthesis conditions and application exploration and experience in the field of lithium ion battery negative electrodes are insufficient. The center of the 8-connected aldehyde porphyrin ligand (TTEP) used in the present invention is a porphine ring. The four substituents on the porphine ring cannot be coplanar due to the steric hindrance effect. TTEP has a symmetrical three-dimensional cubic structure in space, which ensures that the synthesized COF material has a 3D structure, thereby avoiding the stacking problem of 2D COFs materials, making the active sites evenly distributed and fully exposed so as to be fully utilized, and at the same time being able to provide a multi-dimensional ion movement path, with high connectivity and good stability.
[0030] The two building blocks selected by the present invention, the 8-connected cubic porphyrin ligand and tetraaminophenylporphyrin (TAPP), both have a central conjugated large π-electron delocalized ring. The polyimide-based 3D COF material formed by the two has strong conductivity in both parallel and vertical directions, which is conducive to the transfer of charges and can also maintain the stability of the three-dimensional framework. The large plane of tetraaminophenylporphyrin (TAPP) also plays a supporting role in the step-by-step synthesis process, which is conducive to the construction of the three-dimensional framework structure. The synthesis of the 3D COF material prepared by the present invention is as follows Fig.10The high nitrogen content and benzene ring number of the two building blocks, as well as the large number of evenly distributed imine bonds in the 3D structure, can avoid the problem of insufficient utilization of internal active sites caused by stacking problems, alleviate the volume change problem during lithium ion insertion and extraction, and provide abundant lithium storage sites that can be fully utilized while having good stability, thereby achieving excellent lithium storage performance.
[0031] The present invention prepares and synthesizes a [8+4] type 3D COF and applies the [8+4] type 3D COF to lithium battery negative electrode materials for the first time with excellent electrochemical performance. Fig.10 It can be seen from the synthesis steps and geometric expansion structure shown that the [8+4] type 3D COF material synthesized in the present invention, in which 8 and 4 represent the number of functional groups, forms the [8+4] type after condensation between the two functional groups. The 3D [8+4] COF material prepared by the present invention is formed by condensation of 8-connected cubic ligands TTEP and 4-connected square planar building units. Its 3D topological structure can avoid the π-π stacking phenomenon of 2D COFs materials, and has symmetrical cubic nodes, high connectivity, permanent porosity and high specific surface area. However, the presence of benzene rings on general planar 2D COFs causes π-π interactions between layers, causing the layers to be closely stacked. If the interlayer spacing is too small, it is not conducive to the movement and binding of lithium ions, and will also affect the pore size and specific surface area.
[0032] At the same time, it can be seen from the framework structure of the 3D COF prepared by the present invention that there is a structural support between the layers with multi-dimensional channels (such as Fig.10 As shown in the figure, the active sites can be evenly distributed. When used as the negative electrode material of lithium-ion batteries, its 3D porous structure and uniform active sites can promote charge transfer, facilitate the embedding and extraction of lithium ions, inhibit volume expansion, and achieve excellent practical electrochemical energy storage performance. The serious interlayer stacking of planar 2D COF will also cause the active sites (functional groups or C=N bonds, etc.) to accumulate, which is not conducive to ion movement between layers and can only stack pores in the one-dimensional movement direction.
[0033] The present invention focuses on using a 3D COF material prepared by reacting a synthesized 8-connected cubic porphyrin ligand and a 4-connected rectangular TAPP ligand as a negative electrode active material for a lithium-ion battery, exploring a synthesis method for high-quality 3D COF through a highly connected cubic building block, promoting the development of COF materials with a novel topological structure synthesized using a highly connected building block, and greatly enriching the types of 3D COFs. The 3D COF of the present invention has a stable three-dimensional framework structure, which can effectively solve the problem that the serious π-π stacking between the layers of the 2D COF synthesized by traditional triangular and quadrilateral building units causes the aggregation of active sites and a single ion channel, resulting in the inability to obtain good electrochemical performance in practical applications. At the same time, the material framework has a porphyrin center electron-rich delocalized ring in both the horizontal and vertical directions, which can improve the conductivity of the material. This is also the first time that the [8+4] type highly connected 3D COF has been applied in the field of lithium-ion battery negative electrode materials, and has achieved excellent electrochemical performance.
[0034] Traditional COF materials have problems such as poor conductivity and stacking, which cause poor actual electrochemical performance. Usually, a large amount of conductive agent is required to increase the conductivity of the electrode, but this will reduce the energy density (the capacity of carbon conductive agents is relatively low). The stacking problem is traditionally solved by peeling, including mechanical ball milling, but it can only reduce the particle size and stacking to a certain extent, and cannot be fundamentally solved. On the other hand, chemical peeling is usually done by adding other structures and other molecules between the two-dimensional material to relieve the stacking in space, but it may increase steric hindrance, make the synthesis process more complicated, and may affect the conjugation of the COFs skeleton and thus affect the structural stability. Such methods are also very rare and the effect is general. In view of the above problems, the present invention adopts a specific method to use TTEP and TAPP two monomers to form [8+4] type 3D COF for the first time. This material is a 3D framework material, and its structure fundamentally solves the stacking problem and is more stable than the 2D material structure. It can avoid the increase in interlayer spacing caused by the insertion of lithium ions between the layers, thereby causing the poor stability, poor cycle life and safety caused by the change in electrode volume. On the other hand, there is the issue of conductivity. The large π-electron delocalized rings in the horizontal and vertical directions of this material structure can improve the conductivity of the material, thereby improving parameters such as electronic conductivity, avoiding the problem of reducing capacity density due to the incorporation of a large amount of conductive agents. In addition, this material has good electrochemical properties and a very high capacity compared to other such materials.
[0035] Beneficial effects: Compared with the prior art, the present invention has the following advantages:
[0036] The present invention proposes a method for preparing a lithium ion negative electrode material based on a three-dimensional covalent organic framework 3D COF material with 8-connected cubic ligands. Through 8-connected 3D high-connectivity building blocks, a 3D COF material with an interpenetrating three-dimensional topological structure and highly connected permanent voids is synthesized by a solvothermal method. The 3D COF material can be used as a lithium ion negative electrode material, and also provides the possibility for the enrichment of 3D COF materials and their application in various fields.
[0037] The 3D COF lithium-ion battery negative electrode material prepared by the present invention is different from the existing graphite material with low energy density and COFs electrode material with high theoretical capacity, but poor actual specific capacity, low conductivity and stability. The 3D COF material synthesized by the unique cubic ligand of the present material makes the abundant active sites evenly distributed, and the conjugated space framework structure has excellent thermal stability and chemical stability. Its structure fundamentally solves the stacking problem existing in the 2D COF material, and is more stable than the 2D material structure, which can avoid the increase of interlayer spacing caused by the insertion of lithium ions between layers, and then the problems of poor battery stability, poor cycle life and safety caused by the change of electrode volume. On the other hand, the present material has a central conjugated large π-electron delocalized ring in both parallel and vertical planes, provides good charge transfer performance, and achieves high conductivity, stable cycle performance and excellent electrochemical energy storage performance. The [8+4] type high-connectivity 3D COF prepared by the present invention is applied in the field of lithium-ion battery negative electrode materials for the first time, and has achieved excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The building block TTEP of a three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands prepared by the present invention 1 H NMR spectra;
[0039] Figure 2 This is a SEM image of a three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands prepared by the present invention;
[0040] Figure 3 A Fourier transform infrared (FT-IR) image of a three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands prepared by the present invention;
[0041] Figure 4 A polycrystalline X-ray diffraction (PXRD) pattern of a three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands prepared by the present invention;
[0042] Figure 5 A nitrogen adsorption-desorption (BET) diagram of a three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands prepared by the present invention;
[0043] Figure 6 A three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands prepared by the present invention is subjected to a high-temperature reaction at 200 mA g -1 Performance diagram after 250 cycles at a current density of ;
[0044] Figure 7 A three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands prepared by the present invention is subjected to 1000 mA g -1 Performance diagram after 1000 cycles at a current density of;
[0045] Figure 8 The rate performance of a three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands prepared by the present invention at different current densities;
[0046] Fig. 9 A three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands prepared by the present invention is in the range of 0.01-3.00 V with a scan rate of 0.2 mV s -1 Cyclic voltammetry curve of
[0047] Fig.10 The invention discloses the synthesis steps and framework structure of a three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands. DETAILED DESCRIPTION
[0048] The present invention is further described below in conjunction with specific embodiments and drawings.
[0049] The experimental methods described in the examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0050] Among them, 3,5-dibromobenzaldehyde, pyrrole, methanol, p-acylphenylboronic acid, tetrahydrofuran (THF), anhydrous potassium carbonate, propionic acid and dichloromethane (DCM) were all purchased from Titan Technology Exploration Platform. Ketjen black, polyvinylidene fluoride (average molecular weight 400,000-500,000), N-methylpyrrolidone (NMP), mesitylene, glacial acetic acid, 5,10,15,20-tetraaminophenylporphyrin (TAPP), and tetrakis(triphenylphosphine)palladium (0) were all purchased from Aladdin Chemical Reagent Network.
[0051] Example 1
[0052] The specific preparation steps of the three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands are as follows:
[0053] (1) Add 3,5-dibromobenzaldehyde (3.96 g, 15 mmol) and 200 ml of propionic acid into a 500 ml double-necked round-bottom flask.2 Stir and dissolve under protection. When the reaction is heated to reflux, 1.1 ml of pyrrole diluted with 10 ml of propionic acid is added dropwise to the reaction system. The reaction system is heated to 140°C and reflux reaction is continued for 3 hours. After the reaction is completed, it is cooled and filtered. The solid is washed with a large amount of methanol and transferred to a vacuum drying oven and maintained at 80°C for 12 hours to obtain a purple product A.
[0054] (2) Product A compound (1 g, 0.8 mmol), p-acylphenylboronic acid (1670 mg, 8.0 mmol), tetrakis(triphenylphosphine)palladium(0) (240 mg, 0.2 mmol) and anhydrous potassium carbonate (2.67 g, 19.2 mmol) were weighed and added into a 250 ml double-necked round-bottom flask. The mixture was degassed three times under an argon atmosphere. THF (70 ml) and H2O were added to the reaction system. 2 O (20 ml), the reaction was heated to 100 ° C and stirred for 48 hours. 50 ml of DCM was added to the mixture for dissolution and extraction three times, anhydrous sodium sulfate was added to the extract to remove water, the mixture was filtered and the filtrate was collected and dried, and recrystallized from dichloromethane and methanol several times to obtain 5,10,15,20-tetrakis(tetrakis(([1,1':3',1"-triphenyl]-4,4"-dicarboxaldehyde)))(TTEP) product.
[0055] (3) TTEP (0.0724 g, 0.05 mmol) and 5,10,15,20-tetraaminophenylporphyrin (TAPP) (0.675 g, 0.1 mmol) were dissolved in a mixture of NMP (2 mL) and 1,3,5-trimethylbenzene (2 mL) and fully dissolved by ultrasonication;
[0056] (4) Add 0.4 mL of 6 M AcOH to the mixture of step (3), transfer the mixture to a Pyrex tube, freeze it quickly with liquid nitrogen (until the solution stops flowing), evacuate it to an internal pressure of 0.15 mmHg, and thaw it. Repeat the cycle of freezing with liquid nitrogen - evacuating - thawing three times. Keep the reaction mixture in a thermostat at 120° C. for 3 days.
[0057] (5) The suspension obtained in step (4) was centrifuged to remove the supernatant to obtain a dark brown precipitate, and then the product was washed by multiple centrifugation and Soxhlet extraction with THF (20 ml × 3 times) and acetone (20 ml × 3 times). Finally, the solid was dried under vacuum at 80° C. for 12 hours to obtain a dark brown solid product, which is a three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands.
[0058] Figure 1 is the cubic building block TTEP of the present invention 1 H NMR spectrum, 1H NMR (400MHz, Chloroform-d) δ10.15–10.05(m,2H),9.06(s,2H),8.60(s,2H),8.35(s,1H),8.13–7.99(m,8H).
[0059] Figure 2 is a SEM image of the 3D COF material prepared by the present invention. Figure 2 It can be seen that the 3D COF material has a flower-like morphology composed of flakes, which is different from the irregular flake stacking morphology of most existing 2D COFs. Figure 3 This is the FT-IR image of the 3D COF material prepared in the present invention. Figure 3 It can be seen that the 3D COF material has a -1 The band at 1696 cm-1 fully proves the formation of a new C=N bond, while the -1 The C=O characteristic peak of TTEP monomer and 3340 cm -1 The NH characteristic bands of nearby TAPP monomers did not appear, which fully demonstrated that the two monomers formed a new substance through the imine bond. Figure 4 The PXRD pattern of the 3D COF material prepared in the present invention is shown in FIG. Figure 4 It can be seen that the 3D COF material exhibits diffraction peaks at 2.74°, 6.42° and 10.42°, indicating the formation of its framework network structure, proving that the 3D COF material with high crystallinity was successfully synthesized. Figure 5 The BET diagram of the 3D COF material prepared in the present invention is shown in FIG. Figure 5 It can be seen that under 77K conditions, using N 2 The specific surface area of 3D COF materials was studied by adsorption isotherm method. In the low pressure range (P / P0<0.05), N 2 The rapid uptake of MgO showed a typical type I isotherm, revealing its microporous nature, its framework structure with high specific surface area and micropore filling phenomenon.
[0060] Example 2
[0061] The electrochemical performance of the 3D COF material prepared by the present invention as a lithium ion negative electrode material is tested.
[0062] Test steps: The 3D COF material prepared in Example 1 is used as the active material. About 35 mg of the active material is weighed according to the mass ratio of active material: conductive agent (Ketjen black): polymer binder (polyvinylidene fluoride, PVDF) of 7:2:1. It is fully ground in a mortar, and about 350 μL of NMP (N-methylpyrrolidone) is added as a solvent to fully dissolve the binder. Stir for 12 hours to mix it evenly to obtain a slurry with a flow tendency; the slurry is coated on the rough surface of the copper foil by a film stretcher. The 150 μm surface is selected for the four-sided film stretcher. The coated film is kept at 80°C in a vacuum drying oven for more than 10 hours to fully evaporate the solvent. The copper foil coated with the active material is cut into electrode sheets with a diameter of 12 mm by a slicer, and the mass of the active material on each electrode sheet is controlled to be about 1.0 mg. For the assembly of lithium-ion batteries, Celgard 2600 and lithium sheets are used as battery separators and counter electrodes, respectively, and the electrolyte is 1 mol L -1 LiPF 6 Solution (ethylene carbonate / dimethyl carbonate / diethyl carbonate V:V:V=1:1:1); the battery was assembled in a glove box at an ambient temperature of 25°C, and the contents of oxygen and moisture were both less than 1ppm. The LAND CT 2001A blue electric system was used for constant current charge and discharge tests, and the CHI660E electrochemical workstation was used for cyclic voltammetry (voltage range 0.01~3.0V, scan rate 0.2mV s -1 ) and impedance (frequency range 0.01Hz~100kHz). Figure 6 The 3D COF material prepared by the present invention is used as a lithium ion negative electrode material at a voltage of 0.01-3V and 200mA g -1 The performance diagram of 250 cycles at a current density of Figure 6 It can be seen that the reversible specific capacity after stabilization is 1190 mAh g -1 . Figure 7 The COF material prepared by the present invention is used as a lithium ion negative electrode material at 1000mAg -1 Performance diagram of 1000 cycles at a current density of Figure 7 It can be seen that the reversible specific capacity is 736 mAh g -1 .
[0063] The ultra-high specific capacity and excellent stability in the low current short cycle and high current long cycle tests prove that the structural characteristics enable the active sites to be fully utilized to bring about excellent energy storage performance and cycle performance. Figure 8 The 3D COF material prepared by the present invention is used as a lithium ion negative electrode material at different current densities. Figure 8 It can be seen that when the current density is 200, 500, 1000, 2000, 4000 and 200mAg -1When , the capacities of the 3D COF electrodes are 889, 517, 442, 298, 222, and 1199 mAh g -1 , proving its excellent rate performance and structural stability. Fig. 9 The COF material prepared by the present invention is in the range of 0.01-3.00 V, with a scan rate of 0.2 mV s -1 The cyclic voltammetry curve of Fig. 9 It can be seen that in the first cathode reduction reaction, there are obvious reduction peaks near 0.30 and 0.73V, which disappear in subsequent scans. This is due to the formation of a solid electrolyte interface (SEI). For the first anodic scan, there are two low-potential anodic peaks at 0.53V and 1.24V. In the following second and third scans, the redox trends are basically the same, indicating that the material has good reversibility. Compared with the first cycle, the redox potential difference after the second cycle becomes smaller, indicating that the polarization phenomenon of the electrode material is weakened and the electrochemical power system has been significantly improved.
[0064] Example 3
[0065] The preparation method of Example 3 is the same as that of Example 1, except that: in step (1), the molar ratio of 3,5-dibromobenzaldehyde to pyrrole is 1:1, the acidic solution is acetic acid, the heating temperature is 130° C., and the reaction time is 4 hours.
[0066] The molar ratio of the product A to the acylphenylboronic acid in step (2) is 1:8, the heating temperature of the reaction is 80°C, and the reaction time is 3 days; the solvent of the reaction is dioxane, and the alkaline metal salt of the reaction is K 2 CO 3 , the catalyst condition is AsPh 3 .
[0067] The molar ratio of TTEP to TAPP in step (3) is 1:2, and the organic solvent is dioxane (2 ml) and mesitylene (2 ml).
[0068] The liquid nitrogen used in step (4) is rapidly frozen and then evacuated to an internal pressure of 0.2 mmHg. The liquid nitrogen freezing-vacuuming-thawing cycle is repeated twice and then the reaction is kept warm at 100° C. for 7 days.
[0069] Example 4
[0070] The preparation method of Example 4 is the same as that of Example 1, except that: in step (1), the molar ratio of 3,5-dibromobenzaldehyde to pyrrole is 1:1.2, the acidic solution is pyridine, the heating temperature is 150° C., and the reaction time is 2 hours.
[0071] In step (2), the molar ratio of the product A to the p-acylphenylboronic acid is 1:10, the heating temperature of the reaction is 120° C., and the reaction time is 1 day; the solvent of the reaction is dioxane and water, and the alkaline metal salt of the reaction is CsCO 3 , the catalyst condition is n-Bu 3 P.
[0072] The molar ratio of TTEP to TAPP in step (3) is 1:3, and the organic solvent is N-methylpyrrolidone.
[0073] The insulation temperature in step (4) is 140° C. and the reaction time is 3 days.
Claims
1. A method for preparing a three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands, characterized in that: The following steps are involved: (1) 3,5-dibromobenzaldehyde and pyrrole are dissolved in an acidic solvent and heated to react to generate product A; (2) reacting product A with p-acylphenylboronic acid to generate product B through Suzuli coupling reaction; (3) dissolving the product B and 5,10,15,20-tetrakis(4-aminophenyl)porphyrin in an organic solvent, and fully dispersing and dissolving them by ultrasonication; (4) adding a catalyst to the mixture of step (3), and then circulating liquid nitrogen to freeze, evacuate, and thaw, and then maintaining the temperature to obtain a suspension; (5) After the suspension is cooled to room temperature, the precipitate is collected by centrifugation and dried to obtain the product [8+4] type 3D COF material; In step (1), the molar ratio of 3,5-dibromobenzaldehyde to pyrrole is 1:1-1:1.2; the heating temperature is 130°C-150°C; and the reaction time is 2-4 hours; The molar ratio of the product A to the p-acylphenylboronic acid in step (2) is 1:8-1:10; the heating temperature of the Suzuli coupling reaction is 80°C-120°C, and the reaction time is 1-3 days; The product B is 5,10,15,20-tetrakis(tetrakis(([1,1':3',1"-triphenyl]-4,4"-dicarbaldehyde))) ligand; The molar ratio of 5,10,15,20-tetrakis(tetrakis(([1,1':3',1"-triphenyl]-4,4"-dicarbaldehyde))) to 5,10,15,20-tetrakis(4-aminophenyl)porphyrin in step (3) is 1:2-1:3; the catalyst in step (4) is acetic acid, the insulation temperature is 100-140°C, and the reaction time is 3-7 days.
2. The method for preparing a three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands according to claim 1, characterized in that: The acidic solution in step (1) is acetic acid or propionic acid.
3. The method for preparing a three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands according to claim 1, characterized in that: The solvent for the Suzuli coupling reaction in step (2) is dioxane, tetrahydrofuran and water or dioxane and water.
4. The method for preparing a three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands according to claim 1, characterized in that: In step (2), an alkaline metal salt and a catalyst are added to the Suzuli coupling reaction; the alkaline metal salt is Na2CO3, K2CO3 or CsCO3; the catalyst is tetrakis(triphenylphosphine)palladium(0), AsPh3, n-Bu3P or Ph2P(CH2)2PPh2(dppe).
5. The method for preparing a three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands according to claim 1, characterized in that: In step (3), the organic solvent is one or more of dioxane, N-methylpyrrolidone, N,N-dimethylformamide and 1,3,5-trimethylbenzene.
6. The method for preparing a three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands according to claim 1, characterized in that: In step (4), the liquid nitrogen is rapidly frozen and then vacuumized to an internal pressure of 0.15-0.2 mmHg. The liquid nitrogen freezing-vacuuming-thawing cycle is repeated 2-3 times and then the reaction is kept warm.
7. A three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands prepared by the preparation method according to claim 1.
8. An application of the three-dimensional covalent organic framework 3D COF material based on 8-connected cubic ligands as claimed in claim 7 in the field of negative electrode materials for lithium-ion batteries.
Citation Information
Patent Citations
Preparation method of conjugated three-dimensional porphyrin-based covalent organic framework material
CN110294843A
Three-dimensional covalent organic framework compound and preparation method thereof
CN113788921A